Activating international humanitarian law in contemporary internationalconflicts (Numerus academy review, 2026)
International armed conflicts existed in antiquity and the present era, although they were united by the issue of the use of armed force, but the foundations of theirestablishment differed, as after it was founded on the colonial conflicts of the territories of other countries in order to gain influence, the ethnic and cultural reasons became. Inaddition to the emergence of armed conflicts that require the application of internationalhumanitarian law, given the failure to observe the standards of international armed conflict .It is also considered the development of new mechanisms at the expense of thesovereignty of states, which have developed through historical times and have become subject to international bodies and organizations tainted by defects in terms oforganization and decision-making authority, but their role in developing the rules of international humanitarian law cannot nevertheless be denied.